Argatroban in patients with acute ischemic stroke with early neurological deterioration: a cost-effectiveness analysis from the perspective of Chinese healthcare system - Yu Xie; Liping Hu; Ping Xu; Xianbin Guo; Junxiu Cai; Min Pan; Jie Tang; Qingtao Gong; Rong Su; Yake Lou; Yan Liu; Li Wang; et al. (Frontiers in Pharmacology)
Background and ObjectiveStudies have shown that argatroban improves 90-day functional outcomes in patients with acute ischemic stroke (AIS) with early neurological deterioration (END). However, its cost-effectiveness in this patient population remains unclear.MethodsA combination of a short-term decision tree and a long-term Markov model was developed to calculate the total cost and effectiveness for Chinese patients with AIS with END treated with intravenous argatroban plus standard therapy or standard therapy alone. Cost data were accessed from our institution, the China National Stroke Registry, and other public sources, while effectiveness data were obtained from the EASE trial and the China Health Statistical Yearbook 2022. The primary outcome was the incremental cost-effectiveness ratio (ICER), with secondary outcomes including total cost, total effectiveness, and incremental effectiveness. One-way sensitivity analysis, probabilistic sensitivity analysis, and scenario analysis were performed to assess certainty, uncertainty, and robustness.ResultsFor Chinese patients with AIS with END, treatment combining argatroban with standard therapy resulted in a lifetime cost of 138,812 Chinese Yuan (CNY), compared to 136,353 CNY for standard therapy alone. The combined treatment achieved 4.19 quality-adjusted life years (QALYs) (equivalent to 8.43 life years), while standard therapy yielded 3.78 QALYs (equivalent to 8.17 life years). This led to an ICER of 5968 CNY per QALY (9367 CNY per life year), below the willingness-to-pay threshold. One-way sensitivity analysis indicated that argatroban’s efficacy was the primary driver of the ICER, consistently remaining below the threshold. PSA showed that argatroban was highly cost-effective in over 99% of cases and dominant in 0.54% of cases. Scenario analysis confirmed the robustness of these findings across various scenarios.ConclusionArgatroban is highly cost-effective for Chinese patients with AIS and END from the perspective of the Chinese healthcare system.